2013
DOI: 10.1002/app.39132
|View full text |Cite
|
Sign up to set email alerts
|

The water vapor sorption behavior of a galactomannan cellulose nanocomposite film analyzed using parallel exponential kinetics and the Kelvin–Voigt viscoelastic model

Abstract: Nanocomposite films have been developed where a galactomannan (guar) matrix was reinforced with cellulose nanowhiskers and plasticized using sorbitol. The properties of these films were compared with films made from guar only. The films were examined using scanning electron microscopy and dynamic vapor sorption. The sorption kinetics properties were analyzed using parallel exponential kinetics (PEK) and this data interpreted using the Kelvin‐Voigt (K‐V) viscoelastic model. Substantial differences in sorption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
4
18
0
3
Order By: Relevance
“…This model predicts that as the difference between the isotherm temperature and the T g decreases, there is a corresponding reduction in sorption hysteresis, as has been observed [25]. The model also predicts that sorption hysteresis should collapse when the T g of the material is reached, as has also been recently demonstrated [29]. The T g of gel materials, such as collagen, will decrease with increasing moisture content, because the swelling of the micropores caused by the presence of the sorbate in the matrix creates void volume around the relaxing segments.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…This model predicts that as the difference between the isotherm temperature and the T g decreases, there is a corresponding reduction in sorption hysteresis, as has been observed [25]. The model also predicts that sorption hysteresis should collapse when the T g of the material is reached, as has also been recently demonstrated [29]. The T g of gel materials, such as collagen, will decrease with increasing moisture content, because the swelling of the micropores caused by the presence of the sorbate in the matrix creates void volume around the relaxing segments.…”
Section: Introductionsupporting
confidence: 50%
“…Therefore, the fast process is described by a linear driving force mass transfer diffusion model [28], while the slow process is linked to relaxationlimited kinetics, in which molecular relaxation processes in the cell wall macromolecules are the rate limiting steps. Further support for this interpretation of the PEK model being associated with two different physical processes comes from the observation that the PEK model cannot be applied in materials above T g [29].…”
Section: Introductionmentioning
confidence: 84%
“…This occurs around 65-75% RH at room temperature (Engelund et al 2013;Irvine 1984;Kelley et al 1987;Olsson and Salmén 2004). For instance, Keating et al (2013) reported sorption hysteresis to vanish in man-made hemicellulose (galactomannan) films above 75% RH at 25°C, and this RH level corresponded with the softening point characterised by dynamic mechanical analysis. It can therefore be tempting to associate the decrease in hysteresis for wood above 75% RH, as observed in several studies when desorption was initiated from 90 to 95% RH, with softening of the hemicelluloses.…”
Section: Sorption Hysteresismentioning
confidence: 96%
“…Based on the conceptual framework of Vrentas and Vrentas (1996), it has been suggested that sorption hysteresis is related to the mechanics of shrinkage and swelling of the cellulosic cell walls during changes in moisture content (Engelund et al 2013;Hill et al 2009Hill et al , 2012a. The exact mechanism is not fully understood, but an important aspect is assumed to be the glass transition (softening) of constituent cell wall polymers (Engelund et al 2013;Keating et al 2013;Salmén and Larsson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Guar gum film shows Fig. 6 Oxygen permeability of the films Cellulose pronounced desorption hysteresis in equilibrium moisture content and can act as barrier to air and moisture (Keating et al 2013;Shetty et al 1996). The composite films showed lower WVP than TOCNs film, indicating that the introduction of HPG effectively reduced the WVP of the composite films.…”
Section: Contact Anglementioning
confidence: 97%